Fabrication, Thermal and Sound Absorption Properties of Porous Polyimide Reinforcing by SiO2 Nanoparticles. Issue 1 (March 2021) - Zhao, Yalin; Geng, Mingxin; Ma, Jiangang; Peng, Longgui
Abstract: Special requirements of the service environment put forward higher requirements for the comprehensive performances of porous sound-absorbing materials. In this study, the polyimide/nano-SiO2 composite foams were prepared based via the sol-gel and foaming methods. The effect of different addition of SiO2 nanoparticles on the pore structure, sound absorption properties as well as the thermal properties of polyimide/SiO2 nanocomposite foams are studied. Results indicate that: the addition of the nano-SiO2 particles not only could improve the thermal stability of the composites, but also increase the sound absorption performances. Particularly, the samples with 2% addition of SiO2 nanoparticles shows the optimal thermal and sound absorption performance. Therefore, adding the SiO2 nanoparticles into the polyimide foams is an efficient way to improve its thermal and sound absorption performance, which would give insights into designing sound-absorbing materials with excellent comprehensive performance to curb the noise pollution.